(untitled) (Transport systems and technologies, 2018)
The reliability of the axle boxes is largely due to the reliability and durability of the bearings. With more than a long experience of operating cylindrical bearings with short rollers of type 2726 in the axle boxes of freight cars it is established that their nominal (calculated) durability is higher than their actual service life. The purpose of the article is to determine the loads acting on the bearings of the axle boxes of freight cars taking into account the operational factors. To determine the load acting on the bearing of the axle box of a freight car, the joint action of the vertical forces was taken into account. These forces coincide in direction and are transmitted directly to the busiest bearing of the axle box. It is assumed that these forces arise when the car passes the curve of the section of the track and the interaction of the cars in the train. The have been received the results of calculating the load on the axle boxes and the equivalent dynamic load on the bearing at various speeds and the modes of loading of the universal four-axle car. The action of each component of vertical forces on the overall result has been given. The above studies will make it possible to evaluate durability of cylindrical bearings with greater accuracy and make it possible to have a further correction of the well-known building models in machinery to determine durability of bearing boxes of freight cars to the actual conditions of their operation.